The Development of a Qur'an-Based Learning Model in Astrophysics Lectures to Internalize Religious Character Values (A Hypothetical Model for Astrophysics Lectures) - Zainuddin Zainuddin; Syihabuddin Syihabuddin; Aminuddin Prahatama Putra; Nahadi Nahadi (Jurnal Penelitian Pendidikan IPA, 2025)
This research proposes a Prophetic Learning Model that integrates the religious values of the Qur'an in astrophysics learning to deepen students' scientific understanding and form religious character. The main objective of this research is to develop a model that connects scientific knowledge with spirituality and internalizes religious character values such as faith, piety, patience, gratitude, and cooperation. The method used is a qualitative literature review with an analysis of learning theory, Islamic education concepts, and relevant Qur'anic verses. The results of the study found that the Prophetic Learning Model with stages: Inviting to purify the soul by praying; Reciting verses in the form of kauliah verses with dhikr; Teaching the book in the form of kauniah verses by thinking; Teaching wisdom by thinking and dhikr; and Reflecting on learning by assessing yourself. This model improves students' scientific understanding and strengthens their religious character and social skills. Challenges in its implementation include the difficulty in connecting Qur'anic verses with scientific concepts and the readiness of lecturers and students to adopt this new approach. This model has great potential to develop a more integrative learning experience. This study recommends further trials to evaluate the effectiveness and practicality of the model in the context of higher education, particularly in physics education study programs.